2020
DOI: 10.3390/cells9122623
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-Astrocyte Interactions in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease. PD patients exhibit motor symptoms such as akinesia/bradykinesia, tremor, rigidity, and postural instability due to a loss of nigrostriatal dopaminergic neurons. Although the pathogenesis in sporadic PD remains unknown, there is a consensus on the involvement of non-neuronal cells in the progression of PD pathology. Astrocytes are the most numerous glial cells in the central nervous system. Normally, astrocytes protect neurons by rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 244 publications
(297 reference statements)
0
81
0
Order By: Relevance
“…In these diseases, chronic exposure to ROS and dysregulated signaling between astrocytes, CNS endothelial cells, and pericytes cause the barriers to become hyperpermeable, allowing the invasion of monocytes and other peripheral immune cells into the CNS ( 65 , 66 ). In Parkinson’s disease (PD), increased BBB permeability may be attributed to α-synuclein-induced dysfunction in astrocytes ( 67 ) – the PD-associated α-synuclein (A53T) mutation has been found to cause BBB breakdown and neurodegeneration when selectively expressed by astrocytes in a mouse model ( 68 ).…”
Section: Blood-brain and Blood-cerebrospinal Fluid Barriersmentioning
confidence: 99%
“…In these diseases, chronic exposure to ROS and dysregulated signaling between astrocytes, CNS endothelial cells, and pericytes cause the barriers to become hyperpermeable, allowing the invasion of monocytes and other peripheral immune cells into the CNS ( 65 , 66 ). In Parkinson’s disease (PD), increased BBB permeability may be attributed to α-synuclein-induced dysfunction in astrocytes ( 67 ) – the PD-associated α-synuclein (A53T) mutation has been found to cause BBB breakdown and neurodegeneration when selectively expressed by astrocytes in a mouse model ( 68 ).…”
Section: Blood-brain and Blood-cerebrospinal Fluid Barriersmentioning
confidence: 99%
“…A1 type astrocytes represent reactive microglia-induced cells in stress or disease conditions and are induced by the release of IL-1, TNF and C1q [ 111 , 121 ]. These reactive cells are detected in injured brain regions, where they lose normal functions, release proinflammatory factors (IL-1, IL-1, and TNF), contribute to inflammatory neurodegeneration, and increase their expression of a cytoskeletal protein called Glial Fibrillary Acid Protein (GFAP) [ 121 , 131 ]. However, there are contradictory results from experiments conducted on animals or the post-mortem brains of PD patients.…”
Section: Innate Immunitymentioning
confidence: 99%
“…However, there are contradictory results from experiments conducted on animals or the post-mortem brains of PD patients. Studies on human PD tissues have displayed null or mild increases of astrocytes and/or GFAP immunoreactivity [ 131 , 132 , 133 , 134 , 135 ]. On the contrary, Parkinsonian animal models undergoing 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) or 6-hydroxydopamine (6-OHDA) treatment have exhibited dramatic astrogliosis [ 131 , 136 , 137 ].…”
Section: Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, an interesting thing to note is that some neurons are vulnerable to this pathologic process compared to others. It is also reported that dopaminergic neurons easily degenerate in regions with less astrocytes [52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 98%